Aggrecan in Cardiovascular Development and Disease. (November 2020) - Koch, Christopher D.; Lee, Chan Mi; Apte, Suneel S.
Aggrecan is a large proteoglycan that forms giant hydrated aggregates with hyaluronan in the extracellular matrix (ECM). The extraordinary resistance of these aggregates to compression explains their abundance in articular cartilage of joints where they ensure adequate load-bearing. In the brain, they provide mechanical buffering and contribute to formation of perineuronal nets, which regulate synaptic plasticity. Aggrecan is also present in cardiac jelly, developing heart valves, and blood vessels during cardiovascular development. Whereas aggrecan is essential for skeletal development, its function in the developing cardiovascular system remains to be fully elucidated. An excess of aggrecan was demonstrated in cardiovascular tissues in aortic aneurysms, atherosclerosis, vascular re-stenosis after injury, and varicose veins. It is a product of vascular smooth muscle and is likely to be an important component of pericellular matrix, where its levels are regulated by proteases. Aggrecan can contribute to specific biophysical and regulatory properties of cardiovascular ECM via the diverse interactions of its domains, and its accumulation is likely to have a significant role in developmental and disease pathways. Here, the established biological functions of aggrecan, its cardiovascular associations, and potential roles in cardiovascular development and disease are discussed.